Thyroid transcription factor 1 and p63 expression is associated with survival outcome in patients with non-small cell lung cancer treated with erlotinib - Svaton, Martin; Fiala, Ondrej; Krakorova, Gabriela; Blazek, Jiri; Hurdalkova, Karolina; Barinova, Magda; Mukensnabl, Petr; Pesek, Milos (Oncology letters, 2020)
While erlotinib is primarily administered to patients with non-small cell lung cancer with sensitizing epidermal growth factor receptor (EGFR) mutations, it is also prescribed to patients with wild type (wt) EGFR in higher lines of treatment. However, there is no predictive marker for erlotinib efficacy in patients with EGFR wt. Certain immunohistochemical (IHC) parameters, including thyroid transcription factor 1 (TTF1) and p63, have been reported to indicate predictive power in patients with EGFR wt. The present study focused on retrospective data from the University Hospital in Pilsen using the TULUNG register. TTF1 and p63 expression data were extracted from the hospital information system and merged with registry data to calculate progression-free survival (PFS) and overall survival (OS) rates. A cohort of 345 patients with adenocarcinoma (ADC) or squamous cell carcinoma (SCC) exhibited similar erlotinib efficacies when TTF1 and p63 were ignored. However, significant differences were reported in PFS and OS rates of a subgroup of 126 patients where TTF1 and p63 parameters were known. In a univariate analysis, group A (ADC TTF1+/p63-) achieved PFS of 2.6 months, group B (SSC TTF1-/p63+) 1.9 months and group C (did not fit into groups A or B, i.e., ADC TTF1-/p63+ or SCC TTF1+/p63-) 1.4 months (P=0.006). Median OS was 14.2, 19.1 and 5.3 months for A, B and C, respectively (P=0.002). Furthermore, a multivariate analysis demonstrated IHC markers to be the only significant parameters for PFS and OS. Group C had a negative prognostic factor for PFS [hazard ratio (HR), 1.812; P=0.02] and OS (HR=2.367; P=0.01). In conclusion, patients with EGFR wt and lung carcinomas without TTF1 and p63 expression typical for ADC (TTF1+/p633-) or SCC (TTF1-/p63+) do not appear to be suitable candidates for erlotinib treatment.
Keywords: erlotinib; prediction; prognostic; thyroid transcription factor one; p63; non-small cell lung cancer